The effects of emissions standards on industry in the short run and long run - Y. H. Farzin (Fondazione Eni Enrico Mattei (FEEM), 2000)
Industrialists often claim that, by rendering firms unprofitable and hence forcing them out of business, stricter emissions standards reduce the industry output and competition. This paper considers situations where firms' pollution reduction increases the industry demand, but because of inability to co-ordinate their emissions reductions, and thus free riding problem, they are unable to act in their own collective interest. For such situations, the paper studies the effects of emissions standards on the equilibrium in an oligopoly market both at the firm and industry level and in the long run as well as short run. It shows conditions under which a stricter standard leads to a larger number of firms in the industry, a greater industry output, and a lower total pollution in the long run; and to higher levels of firms' profits and output in the short run. It also shows that for the industry to survive, a minimum pollution standard may be necessary.
Keywords: H23; D62; D43; Q28; 330; Environmental standard; abatement cost; demand effect; industry output; Umweltstandard; Oligopol; Nachfrage; Theorie